The Importance of Higher and Vocational Education for Students' Future at Kendari City High School - Badia, Bahdin Ahad; Putra, Muhammad Idris; Fathur Rachim, La Ode Muhamad; Rahman, La; Darwis, Mardis; Putra, Fachrizal Cesar; Larobu, Feliks Eldad; Rambak, Ezra Pasereng; Gamsir, Laode Abdul; Defi, Sry; Fatana, Ahmad; Jalil, Abdul; Makkajareng, Nizar Fauzan; Aji, Angga Asteriasti; Hasudungan Simanjutak, Raja Agung (Majalah Pengabdian Indonesia, 2024)
Vocational higher education plays an important role in providing a skilled and work-ready workforce. However, in Kendari City there is still an information gap regarding vocational higher education and career opportunities for graduates. This community service activity aims to introduce vocational higher education and disseminate information on new student admissions in 2024 in high schools in Kendari City. The methods used include presentations, discussions, and brochure distribution. The evaluation of the activity showed an increased understanding of vocational education, as well as an increased interest in pursuing it. The brochures provided were considered informative by the participants. This activity succeeded in increasing high school students' understanding and interest in vocational higher education, as well as providing clear information about the 2024 new student admissions. Results showed a 75% increase in understanding and 60% increase in interest in vocational education. As many as 90% of participants rated the brochure as very informative. It is expected that this activity will have an impact on increasing the number of applicants in vocational study programs and providing a better skilled workforce for industries in Kendari City.